Social Support and Parenting Stress During the Covid-19 Pandemic - Yunisah Yunisah; Rizky Putri Amalia; Ananda Rainy Akram; Marisa Fransiska Moeliono; Fitri Ariyanti Abidin (Universitas Ahmad Dahlan, 2022)
Several studies have documented the pivotal roles of social support as a protective factor of parenting stress. However, the association between those variables in the covid-19 pandemic situation has yet to be understood. The present study aims to examine the type of support associated with parenting stress during the Covid-19 pandemic. Furthermore, we also aim to identify the most important source of support for parents. An online survey provided quantitative data from 334 participants. They are 16.5% father (n = 55) and 83.5% mother (n = 279) who have children aged 2-18 years. The Indonesian version of the Social Support Questionnaire and Parenting Stress Scale was used to measure social support and parenting stress during the Covid-19 pandemic. The findings show that social support has a significant negative association with parenting stress. In terms of type, companionship support is significantly associated with parenting stress. The prominent support figure for fathers is their spouses, while family became the primary source of support for mothers. The findings can contribute to a better understanding of the support needed by parents during the covid-19 pandemic.